Хилийн массивын хэт суурилаг, суурилаг найрлагатай чулуулгийн петрографи, геохими ба геохронологи - Т.Оюунчимэг; Д.Шарав; Д.Эрдэнэчимэг; Ц.Наранцэцэг; Н.Ариунаа (Geological Issues, 2025)
This paper presents the field characteristics, petrographic, and whole-rock geochemical data of the ultramafic-mafic rocks of the Khiliin massive, located along the border of north-eastern Mongolia. A petrographic study reveals that ultramafic rocks are represented by dunite, harzburgite, and wehrlite, while the mafic rocks are identified as pyroxenite and gabbroids. Geochemically, the ultramafic rocks are characterized by high MgO (27.0-38.7 wt.%), Fe2O3t (9.35-17.4 wt.%), and low total alkali (K2O+Na2O =0.08-0.24 wt.%) contents, whereas the mafic rocks have low contents of MgO (5.2-20.1 wt.%), Fe2O3t (6.6-10.2 wt.%), high total alkali (K2O+Na2O=0.42-3.95 wt.%) contents. The peridotites of Khiliin massive show enrichment in Th, depletion in Sr, Nb, Zr, whereas the mafic rocks are enriched in Sr, Th, depleted in Nb, suggesting an origin was partial melting of the depleted mantle source. In the Nb/Yb–Th/Yb diagram of tectonic environment, the studied rocks are derived from subduction-related mid-ocean ridge basalts, which formed in supra-subduction zone environments. Zircon U–Pb dating on gabbro show a Late Carboniferous age (304.5±3.2 Ma) for the Khiliin massive.